2021
DOI: 10.1093/genetics/iyab153
|View full text |Cite
|
Sign up to set email alerts
|

The STRIPAK component SipC is involved in morphology and cell-fate determination in the nematode-trapping fungus Duddingtonia flagrans

Abstract: The striatin-interacting phosphatase and kinase complex (STRIPAK) is a highly conserved eukaryotic signaling hub involved in the regulation of many cellular processes. In filamentous fungi, STRIPAK controls multicellular development, hyphal fusion, septation and pathogenicity. In this study we analyzed the role of the STRIPAK complex in the nematode-trapping fungus Duddingtonia flagrans which forms three-dimensional, adhesive trapping networks to capture Caenorhabditis elegans. Trap networks consist of several… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 55 publications
0
13
0
Order By: Relevance
“…Recent studies have shown that the highly conserved Slt2 MAPK of the cell wall integrity pathway ( Zhen et al 2018 ) and the Fus3 MAPK of the pheromone response pathway ( Chen et al 2021 ) both play vital roles in A. oligospora trap differentiation, with Fus3 signaling being essential to induce trap morphogenesis. Moreover, lack of the SipC component of the STRIPAK (striatin-interacting phosphatases and kinases) complex in another species of NTF ( Duddingtonia flagrans ) that forms 3-dimensional traps results in incomplete loop formation and column-like trap structures ( Wernet et al 2022 ). A recent report linked intracellular cAMP signaling to prey sensing in A. oligospora , which demonstrated that deletion mutants of 2 cAMP phosphodiesterases, PdeH and Pdel, resulted in increased cAMP levels during vegetative growth and trap morphogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that the highly conserved Slt2 MAPK of the cell wall integrity pathway ( Zhen et al 2018 ) and the Fus3 MAPK of the pheromone response pathway ( Chen et al 2021 ) both play vital roles in A. oligospora trap differentiation, with Fus3 signaling being essential to induce trap morphogenesis. Moreover, lack of the SipC component of the STRIPAK (striatin-interacting phosphatases and kinases) complex in another species of NTF ( Duddingtonia flagrans ) that forms 3-dimensional traps results in incomplete loop formation and column-like trap structures ( Wernet et al 2022 ). A recent report linked intracellular cAMP signaling to prey sensing in A. oligospora , which demonstrated that deletion mutants of 2 cAMP phosphodiesterases, PdeH and Pdel, resulted in increased cAMP levels during vegetative growth and trap morphogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Of particular interest to nematode-trapping (NT) fungi are the special trapping devices (traps) involved in capturing and killing nematodes ( 13 16 ). The traps are specifically formed by the vegetative hyphae of NT fungi, divided into adhesive knobs and columns, adhesive networks, and constricting and nonconstricting rings according to their different predatory methods ( 17 19 ). Arthrobotrys oligospora is one of the best-known species of NT fungi, which can develop adhesive networks for nematode predation, and its whole genome has previously been sequenced ( 20 ).…”
Section: Introductionmentioning
confidence: 99%
“…One kb flanks homologous to the 5’ and 3’ regions of the gene of interest were amplified by PCR with 25 bp overhangs homologous to either the hygromycin-B ( hph ) or geneticin sulfate (G418, neo ) resistance cassette as well as to the pJET1.2 plasmid backbone. Verification of homologous recombination was performed as described in Wernet et al, 2022 .…”
Section: Methodsmentioning
confidence: 99%